2018
DOI: 10.1177/1098611118783987
|View full text |Cite
|
Sign up to set email alerts
|

Police Body-Worn Cameras: Effects on Officers’ Burnout and Perceived Organizational Support

Abstract: Police departments in the United States are rapidly adopting body-worn cameras (BWCs). To date, no study has investigated the effects of BWCs on police officers themselves, despite evidence suggesting negative effects of electronic performance monitoring on employee well-being. Police officers already experience higher levels of burnout than other professions. We hypothesize that the intense surveillance of BWCs will manifest in how police officers perceive the organizational support of their departments and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 89 publications
(176 reference statements)
2
67
1
1
Order By: Relevance
“…More recently, Baldwin et al (2019), Wassermann et al (2019), and Ermasova et al (2020) have contributed to the study of police officers' stress and psychological/physical health. Related studies have focused more specifically on occupational stress (e.g., Agolla, 2009;Maran et al, 2015;Gutshall et al, 2017;Johnson et al, 2019), while others have investigated police officers' burnout (e.g., Aguayo et al, 2017;Adams and Mastracci, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Baldwin et al (2019), Wassermann et al (2019), and Ermasova et al (2020) have contributed to the study of police officers' stress and psychological/physical health. Related studies have focused more specifically on occupational stress (e.g., Agolla, 2009;Maran et al, 2015;Gutshall et al, 2017;Johnson et al, 2019), while others have investigated police officers' burnout (e.g., Aguayo et al, 2017;Adams and Mastracci, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Following this line, future studies should explore more of the nature of the police job and how it might affect the value assimilating process. For example, specific job characteristics such as body‐worn cameras (Adams & Mastracci, ) and burnout level (Golembiewski, Lloyd, Scherb, & Munzenrider, ) should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the use of BWCs, and officer perceptions surrounding how their agencies could use BWC footage, can influence officer well-being. In their earlier study of the impact of BWCs on officers in five police agencies, Adams and Mastracci (2019b) found that officers who wear BWCs had significantly lower perceptions of organizational support and significantly higher levels of burnout. Furthermore, the relationship between BWCs and burnout was partially mediated by perceived organizational support (Adams & Mastracci, 2019b).…”
Section: Prior Research On the Impact Of Bwcs On Officer Perceptionsmentioning
confidence: 98%